The Learning Management in Buddhism Class Using CIPPA Model Combined with Google Sites for Junior High School Students at Bandung Wittaya School Under the Secondary Educational Service Area Office, Udon Thani - Ruangsomsri, Nisarat; Namseethan, Somkhuan; Saengsai, Prayoon; Wantapho, Natdanai; Rukab, Siriyawan (Journal of Graduate MCU KhonKaen Campus, 2024)
This research aimed to: 1. study the learning management in the Buddhism subject using the CIPPA teaching model combined with Google Sites for junior high school students at Bandung Wittaya School under the Secondary Educational Service Area Office, Udon Thani to achieve an efficiency of 80/80; 2. compare learning outcomes before and after implementing this learning management approach; 3. assess student satisfaction with the learning management in the Buddhism subject using the CIPPA teaching model combined with Google Sites for junior high school students at Bandung Wittaya School under the Secondary Educational Service Area Office, Udon Thani. The sample group comprised 30 students from the first-year secondary school room 1/14. The statistics used for analysis included the Index of Item-Objective Congruence (IOC), E1/E2 efficiency, mean, standard deviation (S.D.), and t-tests. The research results were as follows: 1. Learning management in the Buddhism subject for the first-year secondary school room 1/14 students at Bandung Wittaya School, using the CIPPA teaching model combined with Google Sites for learning unit 2 (on the Buddha's history, Buddhist disciples, exemplary followers, and Jataka tales), achieved an efficiency of 80.46/88.75, exceeding the set 80/80 criteria. 2. The students showed significantly higher learning outcomes after the implementation of the learning management in the Buddhism subject using the CIPPA teaching model combined with Google Sites, with a statistically significant difference at the 0.01 level. 3. Student satisfaction with the learning management in the Buddhism subject using the CIPPA teaching model combined with Google Sites for the first-year secondary school room 1/14 students at Bandung Wittaya School under the Secondary Educational Service Area Office, Udon Thani was at the highest level.